2015
DOI: 10.13189/aeb.2015.030205
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Export Led Growth Hypothesis: Cointegration and Causality Evidence from Sri Lanka

Abstract: This study examines the export led growth (ELG) hypothesis for Sri Lanka on the basis of annual data for the period 1981 to 2012, drawn from the World Bank (WDI) data bank. The period is selected on the grounds that during the period the Sri Lankan economy has been liberalized and in a liberalized economy it is expected that the trade sector plays a key role in national income determination. The hypothesis is tested with simple GDP and GDP net of exports as proposed by Sharma and Panagiotidis (2005). Johansen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Hence, this study finds no evidence to support the validity of the ELG hypothesis for Sri Lanka. The finding of this study is consistent with Abhayaratne (1996); Dilrukshini (2008) and Tahir et al (2015) for Sri Lanka.…”
Section: Table 5: Granger Causality Test Results -Chi Statisticssupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, this study finds no evidence to support the validity of the ELG hypothesis for Sri Lanka. The finding of this study is consistent with Abhayaratne (1996); Dilrukshini (2008) and Tahir et al (2015) for Sri Lanka.…”
Section: Table 5: Granger Causality Test Results -Chi Statisticssupporting
confidence: 90%
“…She employed annual data on GDP, exports, imports, investment and labour for 1960-2015, and adopted VARs for the empirical estimation. Confirming both Abhayaratne (1996) and Dilrukshini (2008), Tahir et al (2015) also found no evidence in support of the ELG hypothesis for Sri Lanka.…”
Section: Empirical Literaturementioning
confidence: 74%
“…Unit root, Granger causality, rolling window techniques are applied and findings show that trade openness index negatively impacts economic growth. Tahir, Khan, Israr, and Qahar (2015) examines time-series data for the period 1981-2012 for Sri Lanka. GDP, Imports, exports, unemployment and investment are used.…”
Section: Empirical Literature On Export-led Growth Hypothesismentioning
confidence: 99%
“…The ultimate objective of any country is to achieve and to sustain economic growth both in the present generation and the upcoming generation (Tahir, Khan, Israr, & Qahar, 2015). Economic growth is highly dependent on the efficient utilization of economy's factors of production.…”
Section: Introductionmentioning
confidence: 99%